2021
DOI: 10.1371/journal.pgen.1009969
|View full text |Cite
|
Sign up to set email alerts
|

Delta/Jagged-mediated Notch signaling induces the differentiation of agr2-positive epidermal mucous cells in zebrafish embryos

Abstract: Teleosts live in aquatic habitats, where they encounter ionic and acid-base fluctuations as well as infectious pathogens. To protect from these external challenges, the teleost epidermis is composed of living cells, including keratinocytes and ionocytes that maintain body fluid ionic homeostasis, and mucous cells that secret mucus. While ionocyte progenitors are known to be specified by Delta-Notch-mediated lateral inhibition during late gastrulation and early segmentation, it remains unclear how epidermal muc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…DeltaB interacts with Notch3 to maintain MG quiescence, thereby acting as a negative regulator of neuron regeneration in the light‐damaged zebrafish retina (Campbell et al , 2021). DeltaC interacts with Notch1a/3 receptors on adjacent epidermal cells to prevent deltaC ( dlc ) expression from those cells, resulting in generating keratinocytes (Lu et al , 2021). Interestingly, previous studies also indicated individual ligands could mediate unique functions not entirely due to the receptor they activate (D'Souza et al , 2008; Choi et al , 2009).…”
Section: Introductionmentioning
confidence: 99%
“…DeltaB interacts with Notch3 to maintain MG quiescence, thereby acting as a negative regulator of neuron regeneration in the light‐damaged zebrafish retina (Campbell et al , 2021). DeltaC interacts with Notch1a/3 receptors on adjacent epidermal cells to prevent deltaC ( dlc ) expression from those cells, resulting in generating keratinocytes (Lu et al , 2021). Interestingly, previous studies also indicated individual ligands could mediate unique functions not entirely due to the receptor they activate (D'Souza et al , 2008; Choi et al , 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Next, we designed genetic interaction studies to explore the relationship between esrrγa and ppargc1a . Suboptimal morpholinos (SOMOs) have been a consistent and well-established strategy to test whether multiple genes operate synergistically in a pathway in multiple species, including zebrafish and Xenopus laevis ( Chambers et al, 2020b ; Choi et al, 2015 ; DiBella et al, 2009 ; Epting et al, 2022 ; Fowler et al, 2021 ; Janssens et al, 2013 ; Kallakuri et al, 2015 ; Lefkopoulos et al, 2020 ; Lu et al, 2021 ; Maerker et al, 2021 ; Tingler et al, 2022 ; Wagle et al, 2011 ). Therefore, we injected SOMO doses of both esrrγa and ppargc1a , based on previously published doses ( Chambers et al, 2018 , 2020b ).…”
Section: Resultsmentioning
confidence: 99%
“…S2B ) or previously published doses ( Chambers et al, 2018 , 2020b ). Suboptimal doses were determined by using half of the optimal dose, as prescribed by previous studies ( Chambers et al, 2018 , 2020b ; Epting et al, 2022 ; Lefkopoulos et al, 2020 ; Lu et al, 2021 ). esrrγa was targeted with two morpholinos: a start site (ATG) morpholino: 5′-CAATGTGGCGGTCCTTGTTGGACAT-3′ (667 µM optimal), and a splice-blocking morpholino 5′-AGGGTAAAAGCCAACCTTGAATGGT-3′ (400 µM optimal, 200 µM suboptimal).…”
Section: Methodsmentioning
confidence: 99%
“…Following thaw, blastocysts were briefly treated with acidic Tyrode's solution (T1788, Sigma) to remove the zona pellucida and placed in pre-equilibrated human IVC1 in eight-well µ-slide tissue culture plates (80826, Ibidi) in approximately 400 µl volume per embryo per well. Half medium changes were done every 24 h. For small-molecule experiments, human IVC1 was supplemented with either 2 µM A83-01 (72022, STEMCELL Technologies) 80,81 , 25 ng ml −1 Activin-A (Qk001, QKINE) [82][83][84] , 200 nM LDN (S2618, SelleckChem) 85,86 , 50 ng ml −1 BMP6 (SRP3017, Sigma Aldrich) 85,86 , 20 µM DAPT (72082, STEMCELL Technologies) [87][88][89][90] , 10 µM Compound-E (ab142164, Abcam) [91][92][93] , 20 µM MK-0752 (S2660, Selleck Chemicals) [94][95][96] or dimethyl sulfoxide (DMSO) for 48 h. In all cases, these concentrations fall within a range of those used for either vertebrate embryos or complex human ES cell-derived models of the embryo. Within these ranges, a low-to-intermediate concentration was selected to avoid non-specific cytotoxic effects while still considering the higher concentration needed for embryo permeation compared with minimal 2D cell culture to achieve inhibitor action.…”
Section: Thawing and In Vitro Culture Of Human Embryosmentioning
confidence: 99%